Simple one pot synthesis of ketone from carboxylic acid using DCC as an activator. Issue 20 (16th May 2019) - Mekonnen, Habtamu Gelaw; Jana, Samaresh
Graphical abstract: Highlights: One pot method. DCC is used as an activator of carboxylic acid. Mild reaction conditions. Aromatic, aliphatic acids react smoothly. Moderate to good yields of the products. Abstract: Simple one pot procedure for the conversion of carboxylic acid to ketone is described. Various carboxylic acids were converted to the corresponding ketones in excellent manner in presence of N, N′-dicyclohexylcarbodiimide (DCC) and organometallic reagents. Aromatic, heteroaromatic and aliphatic acids were converted to the corresponding ketones smoothly under the optimum conditions using organolithium reagents. In this process, desired products have been isolated from the crude reaction mixtures in moderate yields during the purification process.